Educação superior e mercadoria: um estudo sobre as políticas educacionais do Governo Bolsonaro - Rocha, Miliane Pinheiro da (2022)
This dissertation is a scientific research with a qualitative approach. Using the dialectical critical historical materialism of Karl Marx as fundamentais to its development. The object of study of this work is Higher Education and Merchandise: a study on the educational policies of the Bolsonaro government, considering the Capitalist Mode of Production system and the centrality that commodities exert in the social relations developed under its validity. The general objective of this work was to analyze the trajectory of Higher Education in Brazil, considering the historical determinants that insert it into the market circuit, considering the year 2016 as a regulatory framework for the expansion of the privatization of Higher Education until the neoliberal government of Bolsonaro. For this, we developed three specific objectives: to understand how Higher Education enters the commodity circuit and discuss its conception of law and exchange value in capitalist societies; analyze the main trends in Higher Education in Brazil given the context of privatization and Brazilian fiscal adjustment; explain the relationship between Higher Education and Political Economy. In order to achieve these objectives, we seek to answer the following guiding questions: What are the theoretical and political assumptions to legislate Higher Education, and the implications of the State Reform for Education? What is the functionality of Higher Education for Capital? What are the trends in Higher Education in the context of expanded capital reproduction and the mechanisms that lead it to the commodity circuit? Therefore, we carried out a bibliographic and documentary study with the support of scholars in the broad area of Education, as well as with authors who discuss in detail the Education for the Market movement. In order to apprehend the socio-historical formation of Brazilian Higher Education, its formative and constitutive elements that have indications and configurations in the way this type of education currently maintains, we analyze how the Capitalist Production Mode managed to carry out strategies that direct education as an object subject to purchase and sale within the scope of developed social relationships, being articulated with the embryonic processes of the initial form of education. This resumption presented us with the main trends that Higher Education has suffered in the current context of neoliberalism demarcated by the government of Jair Bolsonaro. The results we obtained were based on the historical basis and are fundamental to identify current trends, because from them we perceive the dependent and heteronomous character of higher education in Brazil in relation to countries with central capitalism. It is an education with classist traits, where historically it has been configured as a privilege and in the design of our study, we conclude that it has continuity. After all, the expansion that has been commonly discussed, of access to education, does not guarantee the permanence of teaching, nor is training critically encouraged, but only as a production and self-reproduction of the capitalist system, insofar as education is also an ideological apparatus and the training of the workforce – which has been oriented and directed towards the market. Not surprisingly, distance education is defended as sufficient to the detriment of face-to-face education. There are, therefore, two education projects in dispute: one for social formation, construction of knowledge and the other for training and control of the workforce for capital.